2021
DOI: 10.1177/1054773821994851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Educational Comic Story about Preoperative Orientation on Information and Anxiety Level of Children Undergoing Surgery

Abstract: Surgery is considered a stressful experience for children because of their unfamiliarity with the environment and medical procedures. Anxiety interferes with anesthesia induction and results in many complications. Comic stories produce cognitive control by developing realistic expectations and correcting misperceptions and misbeliefs. This study aimed to assess the effect of an educational comic story about preoperative orientation on the information and anxiety levels of children undergoing surgery. A quasi-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…In this study, we investigated an approach that integrated several previous relatively independent approaches to provide children with an active participatory [23][24][25][26], multimedia-based home-initiated educational intervention prior to admission. Since this experiment incorporates parents and includes three aspects of children's audio-visual stimulation, active painting, and reading, it is more effective than other experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated an approach that integrated several previous relatively independent approaches to provide children with an active participatory [23][24][25][26], multimedia-based home-initiated educational intervention prior to admission. Since this experiment incorporates parents and includes three aspects of children's audio-visual stimulation, active painting, and reading, it is more effective than other experiments.…”
Section: Discussionmentioning
confidence: 99%
“…So werden GN bspw. eingesetzt um Kindern eine Bestrahlungstherapie zu erklären (Sueyoshi et al 2018) oder ihnen die Angst vor Operationen zu nehmen (Taha & El-Sayed 2021).…”
Section: Der Einsatz Von Gn Im Bildungskontext Verschiedener Fachbere...unclassified
“…Studies have shown that non‐pharmacological methods (comics, audio‐visual resources, video games, etc.) in the preoperative period are helpful in reducing children's fear, pain and anxiety (Aytekin et al, 2016; Chow et al, 2016; Forouzandeh et al, 2020; Mohamed & Elattar, 2019; Taha & El‐Sayed, 2021). Reading stories, which is one of these methods, is helpful in reducing children's fear and anxiety (Aydın & Uyar, 2021; Bülbül & Arıkan, 2018; Cordray et al, 2022; Durgut, 2021).…”
Section: Introductionmentioning
confidence: 99%